Economic Stability and (or) Economic Growth - A. Ya. Zaporozhan (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The article is devoted to consideration of two directions of state economic policy — maintaining economic stability and ensuring economic growth. The coronavirus pandemic has divided the world into “before and after”. In the previous period, the financial policy in Russia was based on the principle of macroeconomic stability. It would seem that the macroeconomic stability that has existed for several years has created the basis for economic growth in the country, but it has not been possible to realize the growth potential of the Russian economy. Economic stability is an important criterion for the economy. Only economic stability can be different.The economic stability of the Russian economy in the previous period is the economic stability of stagnation, because the cornerstone of the economic stabilization policy was maintaining a low inflation rate by artificially slowing down demand. N ow this economic stability of stagnation was overturned by the coronavirus epidemic due to a decrease in budget revenues and an increase in budget spending, which results in the threat of inflation.The purpose of the article is to substantiate the necessity and possibility of transition to a new form of economic stability — economic growth stability